Recent Insights on Biological and Ecological Aspects of Ectomycorrhizal Fungi and Their Interactions - Mello, Antonietta; Balestrini, Raffaella (Frontiers in Microbiology, 2018)
The roots of most terrestrial plants are colonized by mycorrhiza-forming symbiotic fungi. They play a key role in terrestrial environments influencing soil structure and ecosystem functionality. Around them a peculiar region, the mycorrhizosphere, develops. This is a very dynamic environment where plants, soil and microorganisms interact. Interest in this fascinating environment has increased over the years. For a long period our knowledge of the biology and diversity of microbial populations in the rhizosphere has been limited, because it has always been linked to traditional culture-based techniques. These methods, which only allow the study of cultured microorganisms, do not allow the majority of the organisms existing in nature to be characterized. Over the last few years, this limitation has been overcome through the introduction of methodologies that are independent of culture techniques. This together with the development of high-throughput molecular tools has given new insights into the biology, evolution, and biodiversity of mycorrhizal associations, as well as, the molecular dialogue between plants and fungi. The genomes of many mycorrhizal fungal species have been sequenced so far allowing to better understanding the lifestyle of these fungi, their sexual reproduction modalities and metabolic functions. The possibility to detect the mycelium and the mycorrhizae of heterothallic fungi has also allowed to follow the spatial and temporal distributional patterns of strains of different mating types. On the other hand, the availability of the genome sequencing from several mycorrhizal fungi with a different lifestyle, or belonging to different groups, allowed to verify the common feature of the mycorrhizal symbiosis as well as the differences on how different mycorrhizal species interact and dialogue with the plant. Here, we will consider the aspects described before, mainly focusing on ectomycorrhizal fungi and their interactions with plants and other soil microorganisms.